The Influence of School Infrastructure on Student Learning Achievement - Hidayah, Anisatul Anisa; Ramadhan, Syahrul (Mentari : Journal of Islamic Primary School, 2025)
The study aims to analyze the influence of school infrastructure on students’ academic achievement. The issue of education quality involves many factors, one of which is the lack of adequate school infrastructure to achieve the goals of the learning process. The research employed a quantitative method using a linear regression model with the help of JASP (Jeffrey’s Amazing Statistics Program) version 0.16.30. The data were obtained from the 2018 PISA (Programme for International Student Assessment) results, focusing on the relationship between inadequate school infrastructure and students’ learning outcomes. The findings of the study indicate that school infrastructure has an effect on academic achievement in the 2018 PISA (Programme for International Student Assessment) results. It was concluded that there is a positive and significant influence between school infrastructure and students’ academic achievement, thus the alternative hypothesis (Ha) is accepted. In this context, school infrastructure serves as a facility that directly supports the educational process in achieving its goals. The completeness of facilities in a school supports the learning process, enabling students to optimize their thinking abilities, which in turn positively impacts their academic achievement.